Role of Programmed Cell Death-1 and Programmed Cell Death Ligand-1 immune checkpoint biomarkers among chronic Hepatitis C virus patients under Hemodialysis s patients under Hemodialysis - Joda, Ryiam S.; Ibrahim , Basim M.; Al-Khafagi, Ahmed F. (Journal of the Faculty of Medicine Baghdad, 2023)
Background: Hepatitis C virus (HCV) infection is one of the most common infections associated with chronic kidney disease (CKD) patients undergoing hemodialysis (HD) in Iraq.Objectives: To determine the prognostic factor value of Programmed Cell Death-1 (PD-1) and Programmed Cell Death Ligand-1 (PD-L1) immune checkpoint biomarkers among CKD patients with HCV infection under HD.Methodology: ELISA technique was used for the measurement of the above-mentioned biomarkers in the serum of 90 Iraqi patients. The participants were divided into three groups; group I included 30 patients infected with HCV without antiviral treatment, group II included 30 patients infected with HCV with recent/previous antiviral treatment, and group III included 30 patients without viral infection (control group).Results: Serum levels of the measured biomarkers were elevated among all the participants, and highly statistical significance differences were found between patients with no treatment. The area under curve (AUC) of PD-1 was 99% and for PD-L1 was 96%. Conclusions: The PD-1 and PD-L1 immune checkpoint biomarkers have excellent prognostic factor-value as predictors for patients with CKD on HD infected with HCV.